The Day in Court: Legal Education as Sociolegal Research Practice in the Form of an Ethnographic Study - Klaus A Ziegert (Legal Education Review)
According to Eugen Ehrlich, one of the acknowledged predecessors of modern sociology of law at the turn of this century, the most important virtue of the accomplished lawyer was to be a “sharp eye for the essence of the societal processes in the present, a high sensitivity for the needs of today and a relationship to the historical fact in law”. l He contrasted this with the proverbial sharp wit of a lawyer which he considered to be “one of the most fruitless of the gifts of human intellect”. There cannot be any doubt that Ehrlich had a lawyer in mind who was an expert on context rather than on mindless detail. However, the target of Ehrlich’s attack was not lawyers as such, but the ossified institutions which produced them. Sociology of law as a new, and as Ehrlich postulated, scientific approach to legal practice had to change those institutions and their kind of legal education. Today, nearly at the end of the century which saw the unfolding of sociology of law, we can confidently say that neither the lawyers nor the institutions which produce them have changed all that much. As far as there was change in legal education, it owes very little to sociology of law and a lot to how legal education has always operated. There have been the perennial curriculum reviews and reforms; new courses and new legally relevant assessments of context have been introduced in law schools; new confrontations with different theory and critical analysis have entered the old scene. But it is highly doubtful whether all of this has had the fundamental emancipative effect which Ehrlich had in mind. And it remains doubtful, and certainly institutionally irrelevant, why lawyers would need a sharp eye for the essence of societal process, once one goes beyond the rhetoric of curriculum reform. A sociological observation of legal education leads to the rather trivial conclusion that legal education does not change much as long as legal systems do not change much and that legal systems do not change much as long as they are designed to operate legal decisions normatively. This conclusion is less trivial for those who, like Ehrlich, want to overcome the extremely powerful definition of legal education by legal practice, a practice which cannot be explained by legal theory other than by reference to further legal practice. For the purpose of legal theory, law is defined as what statutes, judges and administrators say. Those academic lawyers who feel the limitations of reproducing legal education as a theory of legal practice are caught in a dilemma. They can observe and teach law from a position outside legal practice and legal education, and with reference to social or any other scientific theory. However, these references are of little consequence to legal practice and they tend to become marginalised in legal education. Alternatively, they can observe and teach law from a position within the legal system and with reference to legal theory and legal practice. However, these references are of little use to law students. They do not explain the operation of law better than students get to know by internalising legal work practices while passing through law school. A result of the law teachers dilemma is that the use of any other than legal theory — from the critical application of social theory by the European Freirechtsschule and the American or Scandinavian Realists in the past to the application of anti-institutional theory by the Critical Legal Studies movement in the present — is either carved up in legally relevant titbits or is dogmatically purified for consumption in law school classes. In neither case do social sciences, and least of all sociology of law, perform a particularly emancipative job. It is much more likely, in each case, that they are subsumed under the requirements of legal practice to be practical, to give immediate answers and not to ask too many awkward questions. One way out of the dilemma of law teachers and faculties is to conduct legal education as legal studies rather than as a theory of legal practice. This approach posits that, in order to understand and learn the operation of law, it is not enough to internalise legal practice. Law must be seen and studied as a social practice. As such, law is part of social organisation at large, its historical processes and its evolutionary differentiation. For the legal studies approach to succeed, it is necessary to leave sociological theory intact even if used in the jurisprudential domain. Further, the legal studies approach posits — and this takes us back to Eugen Ehrlich — that the application of sociological theory is a “hands on” experience for the law student. This means that, learning law is experienced as a sociological observation of the social practice of law which can be conducted by the students themselves just as much as dogmatic expertise is trained successfully only where the law student learns to argue successfully by imitating legal practice. This is an attempt to achieve more than simply placing the sociological or sociolegal course alongside others ready for rote learning; that is, a course which just equips the law student with the dogmatic wisdom of the history of ideas of sociology of law, a hotch-potch of possible theoretical approaches, a collection of sociological “buzzwords”, a knowledge of the literature of major sociolegal studies and, at best, a hit-list of social science research techniques. Instead, the integrity of constructing sociological theory can also be preserved in a legal education environment if the use of sociological theory is practised. Practice demonstrates to law students that sociological theory is as much or as little the final word on the social reality of law as a statute or a judicial decision is the final conclusion on the legal reality of law. Law students will learn to understand that the use of sociological theory is only meaningful if it ties in with (practical) social science research observations, and that research can only be meaningful if it is guided by theory. Also lawyers, as much or as little as sociologists, do not develop sharp eye for social process just by looking into books. In sum, legal education — if it wants to be committed to organising practical sociological knowledge for lawyers as the legal studies approach suggests it should be — should not be allowed to have sociology of law taught as legal doctrine in the disguise of “interdisciplinary approaches” and with reference to some alleged requirements of legal practice.